Βιβλιοκρισία:Eustathios of Thessalonike Commentary on Homer’s Odyssey, edited by E. CULLHED. Volume I. On Rhapsodies A-B [Acta Universitatis Upsaliensis. Studia Byzantina Upsaliensia 17], Uppsala 2016 - ΛΑΜΠΑΚΗΣ, Στυλιανός (Byzantina Symmeikta, 2019)
Βιβλιοκρισια:Eustathios of Thessalonike Commentary on Homer’s Odyssey, edited by E. Cullhed. Volume I. On Rhapsodies A-B [Acta Universitatis Upsaliensis. Studia Byzantina Upsaliensia 17], Uppsala 2016, σελ. ΧΧΧ+58*+472